Agile PM and BIM: A Hybrid Scheduling Approach for a Technological Construction Project. (2015) - Tomek, Radan; Kalinichuk, Sergey
Abstract: This paper introduces synthesis of the Agile Project Management and Building Information Modeling in construction industry and its practical application with the accent on economic incentives of their implementation as the most significant factor. The executed synthesis of both concepts' features leads to the representation of the general process of integration, thereby the general development of integrated product and process model for addressing the on-site management phase of a construction project. That is when Building Information Modeling technology plays a key role in Agile method not only as the technological container for information model of a construction project, but as a new construction approach bringing in the additional benefits described in the literature.